From progress to nightmare - European regional unemployment over time - Beyer, Robert (Amsterdam, 2015)
"We analyze the distribution of regional unemployment in Europe over the last three decades using non-parametric kernel densities and stochastic kernels. In addition, we employ a multi-level factor model to separate European, country, and region-specific unemployment fluctuations. Three phases of distributional change of EU relative unemployment rates are detected: they polarized from 1986 to 1996, converged after the introduction of the Euro and have been polarizing again since the outbreak of the financial crisis, having reached the highest levels ever. We find that European fluctuations account for roughly two fifths of the total variance confirming the existence of a European unemployment cycle. Country fluctuations are equally important, which leaves one fifth to be explained by region-specific movements. German regions are found to respond negatively to the European factor and country movements cause diverse responses in particular in Italy and England. The convergence prior to 2007 can be attributed to country affects and the divergence thereafter both to country and region-specific factors. Finally, we also discuss within country heterogeneity."